Analysis of intestinal microorganisms and metabolite in childhood allergic asthma: role in assessing the severity of condition in children - Xu, Zhoubin; Ma, Haichao; Liu, Yujuan; Liang, Shiming; Liao, Zhongnan (Frontiers in Pediatrics, 2025)
BackgroundChildhood allergic asthma is a widespread chronic respiratory condition that is becoming more common worldwide. Presently, the evaluation of its severity depends on clinical symptoms and inflammatory indicators like neutrophils and CRP, which are not very specific. Increasing research indicates that the gut microbiota and its metabolites—such as Bifidobacterium, Lactobacillus, short-chain fatty acids, and lipopolysaccharides—are important in immune system regulation and might affect asthma severity through the gut–lung connection. This study aims to determine if these microbial and metabolic factors can be used as new biomarkers to assess the severity of allergic in children.MethodsA retrospective analysis was conducted on the medical records of 148 pediatric patients diagnosed with allergic asthma who were admitted to our hospital between May 2023 and September 2024. The patients were categorized into mild-to-moderate and severe-to-critical groups according to established severity grading criteria during the acute exacerbation phase. Metabolite indices of intestinal microbiota were compared between the two groups, and correlation scatter plots were generated to examine the association between these metabolites and disease severity. Subsequently, a receiver operating characteristic (ROC) curve was constructed to evaluate the predictive value of intestinal microbiota metabolites for assessing the severity of allergic asthma in children.ResultsNo significant differences in neutrophil/leukocyte counts, CRP, or Klebsiella prevalence were observed between the mild-moderate and severe-critical pediatric allergic asthma groups (P > 0.05). However, the mild-moderate group showed significantly higher levels of Bifidobacteria, Lactobacillus, acetic acid, propionic acid, and butyric acid, but lower Escherichia coli and lipopolysaccharide (LPS) than the severe-critical group (P < 0.05). Disease severity negatively correlated with Bifidobacteria, Lactobacillus, and these three short-chain fatty acids, and positively with E. coli and LPS (P < 0.05). For predicting severity, the area under the curve (AUC) was 0.686 for Bifidobacteria, 0.785 for Lactobacillus, 0.811 for E. coli, 0.711 for acetic acid, 0.653 for propionic acid, 0.788 for butyric acid, and 0.671 for LPS. Notably, a combined model integrating these markers achieved an AUC of 0.956, significantly outperforming any single predictor (P < 0.05). These results indicate that gut microbiota-derived metabolites hold substantial potential as biomarkers for assessing disease severity in children with allergic asthma.ConclusionThe composition of intestinal microbiota and their metabolites exhibits abnormal expression patterns in children diagnosed with allergic asthma, correlating with the severity of the disease. These alterations may serve as significant biomarkers for predicting the clinical severity in pediatric patients with allergic asthma.